A step-down nesting-type ac-ac converter combined with voltage equalizers and switched-capacitor simple converters - Kei Eguchi; Ratanaubol Rubpongse; Akira Shibata; Takaaki Ishibashi; Farzin Asadi (Energy Reports, 2020)
In this paper, we present an inductor-less direct ac-ac converter with improved nesting-type topology. Unlike existing direct ac-ac converters, the proposed ac-ac converter combines a voltage equalizer and a switched-capacitor (SC) simple converter. Owing to the nesting conversion using two techniques, the proposed converter can provide a stepped-down voltage with small number of circuit components and high input power factor. To evaluate the performance of the proposed ac-ac converter, we compared the proposed ac-ac converter with existing inductor-less ac-ac converters, namely, flying capacitor type converter, symmetrical type converter, and traditional nesting-type converter, by theoretical analysis and simulation program with integrated circuit emphasis (SPICE) simulations. The SPICE simulations demonstrate that the proposed ac-ac converter outperforms existing inductor-less ac-ac converters in the point of circuit size and input power factor, although the power efficiency of the proposed ac-ac converter is inferior to that of the symmetrical type converter. In the case of 1/4 voltage gain, the proposed ac-ac converter achieves about 82% power efficiency and 0.58 input power factor when the output power is 200 W.
Keywords: 330; Inductor-less ac-ac converter; Nesting-type inverter; Step-down converter; Switched-capacitor circuits; Voltage equalizers